Glossophobia and Engagement in Oral Recitation Among ESL Learners - Bialen, Vincent B.; Alabat, Fairodze G.; Gallogo, Nahara A.; Escolta, Monibina S.; Magnaye, Wiljean G.; Tulud, Donnie; Salinas, Myra V.; Tikas, Ebrahim; Silva, Reena L. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research investigates the impact of glossophobia, or fear of public speaking, on the engagement of Grade 11 students during oral recitations at Isulan National High School. The study aims to identify the levels of glossophobia, the challenges students face, and the effectiveness of their coping strategies. Methodology: A descriptive quantitative research design was employed, involving 130 Grade 11 students selected as respondents. Data were gathered using a structured questionnaire that measured physical symptoms, emotional responses, cognitive effects, and behavioral impacts of glossophobia. Statistical analyses, including correlation tests, were conducted to examine relationships among variables. Main Findings: The study found that students experienced moderate to high levels of glossophobia, with emotional and cognitive effects being most prominent. Glossophobia had a significant negative relationship with student engagement in oral recitations. Although students used coping strategies such as preparation and positive self-talk, these were not significantly effective in reducing anxiety. The findings highlight the urgent need for targeted interventions and supportive classroom environments. Novelty/Originality of this study: This study is among the first to comprehensively examine glossophobia among Filipino senior high school students in the context of oral recitations. It uniquely explores both the mediating and moderating variables affecting student engagement, and provides evidence-based recommendations for developing intervention programs to address public speaking anxiety in a digital era.